Ecological risk assessment of heavy metals in surface sediments and their impact on macrobenthos in Asan Bay, South Korea - Liang, Jian; Ma, Chae-Woo; Kim, Kwang-Bae (Frontiers in Marine Science, 2024)
Bay ecosystems with unique economic and ecological value are more vulnerable to heavy metal pollution than other marine ecosystems. In South Korea, rapid economic development has exacerbated heavy metal pollution in bay environments. This study analyzed concentrations of seven heavy metals and the structure of macrobenthic community in Asan Bay. Five heavy metal indices (PLI, Pn, RI, TRI, and MERMQ) were used to assess ecological risk. Additionally, spearman correlation, biota–environment matching (BIO-ENV), and redundancy analysis (RDA) were utilized to determine the influence of heavy metals on macrobenthic communities. Although average concentrations of seven heavy metals were below sediment quality guidelines (SQGs), the average concentration of Cd was close to the threshold effects level (TEL). The nemerow pollution index (Pn) and the potential ecological risk index (RI) indicated that Cd was the primary heavy metal contributing to ecological risk. Spearman correlation, BIO-ENV, and RDA indicated that heavy metals were the main environmental factors influencing macrobenthic communities in Asan Bay. However, five heavy metal indices (PLI, Pn, RI, TRI, and MERMQ) did not show a response to the macrobenthic communities. Overall, low concentrations of heavy metals have a certain negative impact on macrobenthic communities in Asan Bay. This study can serve as an important reference for marine environmental protection and policy-making in Asan Bay.